ChemInform Abstract: Mild Rhodium(III)‐Catalyzed Cyclization of Amides with α, β‐Unsaturated Aldehydes and Ketones to Azepinones: Application to the Synthesis of the Homoprotoberberine Framework. Issue 42 (1st October 2013) - Shi, Zhuangzhi; Grohmann, Christoph; Glorius, Frank
Abstract A novel synthesis of azepinone derivatives by using a Rh‐catalyzed intramolecular annulation reaction of N‐substituted benzamides and α, β‐unsaturated aldehydes and ketones is developed.